A synthesis of the implementation ambivalence of REDD+ in Sub-Saharan Africa and Southeast Asia - Divine Odame Appiah; Stephanie Esinu Adjoa Gbeddy (Forest and Society, 2018)
Reducing emission from deforestation and forest degradation and associated benefits (REDD+), has received much attention as one of the most controversial climate change initiatives, especially by forest fringed community actors in sub-Saharan Africa (SSA) and Southeast Asia, (SEA) who are skeptical of the scheme.The object of this paper is to examine the seeming potential benefits and accompanying risks and challenges of REDD+ on the livelihoods among smallholder farmers in SSA and SEA. The paper espouses the sustainability context of REDD+ projects as pro-poor forest management mechanisms; through the provision of alternative livelihood. This is achieved through critical review and critique of scientific articles, project reports and relevant documents on REDD+ interventions from a worldwide, regional to local scale. The paper identifies projects that seem to solidify claims that REDD+ projects are simply a new form of colonialism; which the West is using to take advantage of vulnerable groups in the South. The paper concludes with the need to actively engage sub-Saharan African and Southeast Asian women in climate change mitigation benefit schemes on account of the expedient role women play in agricultural activities (which may involve deforestation and forest land degradation).